Complications in Deaths due to Nontraumatic Aortic Dissection: Complications of aort dissections - Buğra, Aytül; Daş, Taner; Kerim Buğra, Abdül Kerim; Arslan, Murat Nihat (The Bulletin of Legal Medicine, 2022)
Objective: It is aimed to reveal the demographic characteristics of patients who died due to non-traumatic aortic dissection, the findings that will increase the risk of aneurysm and dissection, and the complications that develop after dissection, in the light of histopathological findings.Methods: 138 cases diagnosed with non-traumatic aortic dissection, whose autopsies were performed between 2014 and 2018, were retrospectively analyzed. Age and gender distribution, body mass index, distribution of dissection types, complications that may develop after dissection in organs, and histopathological changes in the aortic wall were evaluated.Results: Cardiac tamponade was detected in 67.4% (n=93) of the cases, tamponade and hemothorax in 15.9% (n=22) and hemothorax in 11.6% (n=16). 5.1% (n=7) had a bicuspid aortic valve. 28.2% (n=39) had atherosclerosis, 21.7% (n=30) had elastic degeneration, and 10.8% (n=15) had cystic medial necrosis. In 55.8% (n=77), pathological changes in the vessel wall were not reported. There was widespread intraalveolar bleeding in 34.8% (n=48) and focal intraalveolar hemorrhage in 6.5% (n=9). When cardiac findings were examined, myocardial infarction was observed in 2.2% (n=3).Conclusion: In cases of aortic dissection, a detailed macroscopic and microscopic examination should be performed together with the clinical history. Histopathological examination of the dissected area is important in demonstrating the underlying factors. Histopathological findings in the organs may be useful in predicting the complications of the disease. Autopsy has a critical importance not only in recognizing and understanding the disease, but also in determining the treatment methods to be applied for the disease.
Keywords: autopsy; aortic dissection; myocardial infarction; intralveolar hemorrhage